2001
DOI: 10.1103/physrevlett.87.226803
|View full text |Cite
|
Sign up to set email alerts
|

Self-Induced Acoustic Transparency in Semiconductor Quantum Films

Abstract: We develop a quantum theory of the nonlinear interaction between intense surface acoustic waves and electrons in a quantum well in the regime of moving quantum wires and dots. In the quantum nonlinear regime, the sound attenuation exhibits quantum oscillations and dramatically decreases with increasing quantization. In the case of dynamically created electron dots formed by two acoustic waves, the waves can propagate without any dissipation in the limit of high sound intensity and, hence, the electron quantum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Current (9) does not depend on the amplitude of a scattering potential. If the amplitude of the wave goes down the current tends to zero.…”
Section: Metallic Casementioning
confidence: 96%
See 1 more Smart Citation
“…Current (9) does not depend on the amplitude of a scattering potential. If the amplitude of the wave goes down the current tends to zero.…”
Section: Metallic Casementioning
confidence: 96%
“…A related phenomenon is the electron drag by a surface acoustic wave (SAW) [5], [6], [7], [8], [9], [10], [11], [12]. The wavelength of SAW is large as compared with electrons, so the periodicity is less important and electrons are treated as captured into dynamic quantum dots formed by potential minima.…”
mentioning
confidence: 99%
“…A moving array of DQDs with dimensions of ∼ 1 µm can be easily realized by the interference of two SAW beams propagating along the [110] and [11 0] directions, as illustrated in Fig. 2(b) [10,14,17]. The gray scale image in this figure shows a stroboscopic PL micrograph of the DQD array, which propagates along the x = [100] direction with a velocity v DD = √ 2v SAW .…”
Section: Dynamic Quantum Dots -Dqdsmentioning
confidence: 99%
“…[36][37][38][39][40] Surface acoustic waves are being used to trap carriers in dynamically created quantum dots, transport these trapped carriers, and store light. [41][42][43][44][45][46][47][48][49] To exploit these nanomechanical deformations, one must have ways to probe and control them. It has been suggested that sideband cooling via optical absorption by QDs buried in nanomechanical structures could bring the structures to the quantum limit.…”
Section: Introductionmentioning
confidence: 99%